Everyday Science in Action: Training on Simple Research for Enhancing Scientific Literacy among Science Teachers at MA Salafiyah Kajen Pati - Susilawati; Irman Said Prastyo; Hamdan Hadi Kusuma; Ulil Albab; Ulya 'Uyun Latifah (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2026)
Scientific literacy is essential for both teachers and students to understand natural phenomena and make informed decisions in daily life. However, many teachers face challenges in implementing research-based approaches to enhance scientific literacy in their classrooms. This community service project aimed to provide training on simple research methods for improving scientific literacy to science, mathematics, and geography teachers at MA Salafiyah Kajen Pati. Conducted on November 19, 2025, the training involved 17 teachers and introduced the PISA (Programme for International Student Assessment) framework for scientific literacy, encompassing four key components: science content knowledge, science processes, application contexts, and scientific attitudes. The training emphasized the concept of